Το Μεγάλο Καραβάν-Σεράϊ (Büyük Kervansarayι) της Θεσσαλονίκης. Ιστορικές και Αρχαιολογικές μαρτυρίες [PASCHALLIS ANDROUDIS, Historical and archaeological evidence on the great Karavan – Seray ( Büyük Kervansarayι) of Thessaloniki] - Ανδρούδης Πασχάλης (Μακεδονικά, 2011)
In the present article are discussed some issues on the history andarchitecture of a lost ottoman building of Thessaloniki (Selânik) : the BüyükKervansarayı.Built during the fifteenth century, by a high-rank official or by order of asultan, the Kervansarayı was originally a very grand, almost square building,with one gate and a stable at the rear. It was built at two storeys andcontained cells for the merchants and travellers. While the door into the stablefrom the great court was central, the great gate into the han from the streetwas set to one side (to the East) and was therefore off the true axis, the centerof which was marked by a circular pool. The workshops, stables, toilets andcells of the ground floor were sheltered by a colonnade which supported thecovered gallery of the cells of the upper storey.The Büyük Kervansarayı was built of courses of rough-cut stone, withlayers of brick and with thick mortar. The lower cells were mainly forworkshops (some of them were also for storage since they possessed nowindows). The cells at the upper level had one each – except for those at thecorners a fireplace. They were reached by stairs which were masked by theporticoes. The lower arches were round while those above were ogee inshape. The arch of the entrance gate had voussoirs. The long shaded vaults ofthe upper storey formed attractive vistas. Externally, the lines of smallchimney flues added an interesting dimension to the bold façade of thisausterely grand building. The building possessed enough monumentalcharacter to dominate its architectural environment.The Büyük Kervansarayı played for centuries an important economic rolefor the development of Thessaloniki and was demolished in the 1920’s.